(untitled) (UNIZIK Journal of Marketing, 2024)
This research examined the effect of content marketing on customer patronage of online shops. The study’s objective was to determine the significant impact of content marketing on customer patronage. A cross-sectional design was adopted, and primary data were collected using a structured online questionnaire. As it was not possible to obtain the total population for the study, the Cochran formula was employed for sample size determination with an unknown population. A purposive sampling technique was used to select 384 online customers in Abia State, Nigeria. The data were analyzed using descriptive and inferential statistical tools. The analysis revealed that content marketing had a significant positive effect on customer patronage of online shops. Based on these findings, the study concluded that content marketing significantly enhances customer patronage. Among the recommendations, it was suggested that online shops should focus more on the quality and relevance of their advertisements rather than on their quantity.